The influence of scale effect on the deformation parameters of the Duncan-Chang E-μ model for coarse-grained soils: an experimental study - Shen, Xinggang; Li, Xia; Xiong, Zhiming; Du, Jun; Shen, Rui; Jin, Haoran; Jiang, Mingjie; Luo, Qixun; Wang, Chun (Frontiers in Materials, 2025)
The influence of scale effect on the deformation parameters of the Duncan–Chang E–μ model (hereinafter abbreviated as D–C E–μ M) for coarse-grained soils remains challenging to quantify. These parameters play a critical role in predicting deformations in earth-rock dams, which in turn directly affect the safety and durability of such structures. Therefore, mitigating the impact of the scale effect on the deformation parameters of the D–C E–μ M is essential for the safe design of earth-rock dam projects. Previous studies suggest that variations in the maximum particle diameter dmax and the gradation structure are the primary factors contributing to the scale effect. In this study, the influence of scale effect on the mechanical behavior of coarse-grained soils is systematically investigated. Using a continuous gradation equation, 21 sets of specimens with different gradations were prepared by controlling dmax and the gradation area S. A series of triaxial consolidated-drained tests were conducted to analyze the effects of dmax and S on the deformation parameters of the D–C E–μ M. The experimental results indicate that parameters G, K, F, and Rf decrease as the gradation area S increases. In contrast, parameters n and D first increase and then decrease with increasing S, eventually stabilizing beyond a certain threshold. Empirical relationships between each model parameter and S were established. With increasing dmax, the parameters Rf, lgK, n, F, and D increase, whereas G decreases. All parameters exhibit logarithmic relationships with dmax. Based on the similar gradation method, an empirical formula is proposed to predict the deformation parameters of the D–C E–μ M under the influence of scale effect. The applicability of this formula to various types of coarse-grained soils is validated using test data from existing literature. Finally, a method is presented for predicting in situ deformation parameters of the D–C E–μ M based on scaled laboratory test results using the similar gradation approach.